The Education of Little Tree - Carter Forest 1925-1979 (Albuquerque, [New Mexico] University of New Mexico Press, 1986)
The autobiographical remembrances of the author's Indian boyhood with his Eastern Cherokee hill country grandparents during the Great Depression.
"A Zia book."
Reprint. Originally published: New York : Delacorte Press, c1976. With new foreword.
Keywords: Carter, Forrest -- Childhood and youth; Cherokee Indians -- Biography; Indians of North America -- Biography; Novelists, American -- 20th century -- Biography